ANALISIS RASIO PERTUMBUHAN PREMI DAN RISK BASED CAPITAL TERHADAP RETURN ON ASSETS YANG DIMEDIASI OLEH RASIO BEBAN KLAIM PADA PERUSAHAAN ASURANSI - William William; Fredella Colline (Jurnal Administrasi Bisnis, 2022)
During the pandemic, many companies experienced the impact of the pandemic, including insurance companies. This study conducted with a quantitative approach with multiple linear regression analysis method using the SPSS 23. The sample in this study was determined by the purposive sampling method with the criteria of general insurance companies listed on the Indonesia Stock Exchange that reported interim financial statements in Q1 2019 to Q3 2021, so that a sample of 10 companies was obtained. The data obtained in this study are secondary data by downloading the interim financial statements of insurance companies on the Indonesia Stock Exchange website. Hypothesis testing in this study was carried out using the t test and Sobel test. The results of this study indicate that the ratio of premium growth and risk based capital have an effect on return on assets. Then the premium growth ratio and risk based capital have an effect on the claims expense ratio, while the claims expense ratio doesn’t have effect on return on assets and the claims expense ratio is able mediate the effect of the premium growth ratio and risk based capital on return on assets.